TARGETS FOR LOW SES PARTICIPATION IN AUSTRALIAN HIGHER EDUCATION: GEOGRAPHICAL MEASURES AND STATE BOUNDARIES - Koshy, Paul (The journal of contemporary issues in business and government, 2011)
This paper examines the measurement of the socio-economic status of Australian higher education students in relation to the Rudd/Gillard Government’s establishment of enrolment targets for higher education providers in regard to students from low socio-economic status ("low SES") backgrounds. In particular, it discusses area measures of socio-economic status – where a student’s status is determined by the postcode or collection district of the student’s permanent residence. In doing so, the paper outlines issues with the relevance of current area measures which use a national benchmark, particularly in the context of geographical constraints on the draw-pool of Australian higher education providers, where students attend institutions in their own state or territory. The paper introduces a new area measure which uses the individual state or territory as a reference point, as opposed to the current national reference point. This is assessed in relation to existing area measures and the recently announced funding policy by the Gillard Government.